Evaluasi Pembelajaran Berbasis Pendidikan Karakter di Sekolah Dasar - Magdalena, Ina; Nurchayati, Aan; Heni, Nur (YASIN, 2023)
In the current condition where there is an increase in violence among teenagers/society, the use of bad language and words by students, the low respect for parents and teachers, the low sense of individual and group responsibility, the culture of lies/dishonesty, and the existence of Mutual suspicion and hatred between people make character education a priority that must always be strengthened. This study used the library research method. Library research is a type of qualitative research which is generally carried out by not going into the field in searching for data sources. Library research collects data and information through the help of various materials found in the library room. Evaluation of basic education learning based on character education, by instilling character values that are included in the learning process in each subject related to norms or values in the context of everyday life through various real examples. Hopefully by always strengthening character education will produce students who not only have good academic knowledge but also have quality character.